OP0048 GENOME-WIDE META-ANALYSIS REVEALED MULTIPLE NOVEL LOCI ASSOCIATED WITH SERUM URIC ACIDLEVELS IN JAPANESE. (June 2019) - Matsuo, Hirotaka; Nakatochi, Masahiro; Kanai, Masahiro; Nakayama, Akiyoshi; Hishida, Asahi; Kawamura, Yusuke; Nakajima, Mayuko; Kamatani, Yoichiro; Shinomiya, Nariyoshi; Yokota, Mitsuhiro; Wakai, Kenji; Okada, Yukinori
Abstract : Background: Uric acid is an end metabolite of purines which is produced predominantly in the liver and is excreted by the kidneys and the intestine. Genes for urate transporters and proteins associated with cell metabolism might therefore be expected to be associated with serum uric acid (SUA). Indeed, urate transporter genes such as SLC22A12 (also known as URAT1), SLC2A9 (GLUT9), and ABCG2 (BCRP) have been markedly associated with SUA 1, 2, hyperuricemia, and gout 3-5 . To date, several genome-wide association studies (GWASs) of SUA have been performed with some populations including Japanese. Objectives: We have investigated the genetic loci that influence SUA with more than 120, 000 Japanese individuals with a genome-wide meta-analysis and have compared our findings with those of previous GWASs. Methods: We performed a genome-wide meta-analysis based on three Japanese cohorts including those of the Japan Multi-institutional Collaborative Cohort (J-MICC) Study, the Kita-Nagoya Genomic Epidemiology (KING) Study, and the BioBank Japan (BBJ). We also performed the trans-ethnic meta-analysis across the present study and the Global Urate Genetics Consortium (GUGC)-based study to carry out fine-mapping analysis. Results: We identified 8, 948 variants at 36 genomic loci (P<5×10 –8 ) including eight novel loci (Figure 1). Of these, missense variants of SESN2 and PNPLA3 were predicted to be damaging to the function of these proteins; another five loci— TMEM18, TM4SF4, MXD3-LMAN2, PSORS1C1-PSORS1C2, HNF4A —are related to cell metabolism, proliferation, or oxidative stress; and the remaining locus, LINC01578, is unknown. We also identified 132 correlated genes whose expression levels are associated with SUA-increasing alleles. These genes are enriched for the UniProt transport term, suggesting the importance of transport-related genes in SUA regulation. Furthermore, trans-ethnic meta-analysis across our own meta-analysis and the GUGC has revealed 15 more novel loci associated with SUA (Figure 2). Conclusion: Our findings thus provide important insight into SUA regulation and the pathogenesis of hyperuricemia and gout, and they provide a potential basis for the development of new treatments for these diseases. References: [1] Köttgen, A. et al. Nat Genet45, 145-54 (2013). [2] Kanai, M. et al. Nat Genet50, 390-400 (2018). [3] Matsuo, H. et al. Sci Transl Med1, 5ra11 (2009). [4] Woodward, O.M. et al. Proc Natl Acad Sci U S A106, 10338-42 (2009). [5] Nakayama, A. et al. Ann Rheum Dis76, 869-877 (2017). Disclosure of Interests: None declared